O relato de experiência e a formação docente: mapeamento de dissertações e teses (2012 a 2021) - Marcelino Lanfranco, Áurea Cristina Pires (2022)
When we looked for the experience report as a methodology in the CAPES Theses and Dissertations Catalog database, we did not find any work that has mapped the trends of experience reports that are found in the area of education. Therefore, this research aims to defend that the experience report is a research methodology in education. The general objective of this research is to map the theses and dissertations, developed in Brazilian postgraduate courses, which describe experience reports developed in the classroom. The specific objectives are: to analyze the dissertations and theses, which used the experience report as a methodology; how they are being described; and finally, how these descriptions impact the continuing education of the teacher who intends to reproduce this report. This dissertation focuses on the continuing education of teachers, specifically in classroom work, where their experiences and relationships with other more experienced professionals contribute significantly to teacher education. Research that maps productions can significantly contribute to the constitution of the research field, in this case, teacher education. This dissertation is a research that brings results from the State of Knowledge, as the mapping is centered on theses and dissertations. The question that guided this work was “How is the experience report in the training of teachers in Brazilian postgraduate courses treated?”. Talking with the authors Dubar (2005), Fortunato (2018;2021), Nóvoa (2017), Perrenoud (2000), Tardif (2017) and Xavier (2014), it was possible to think, within the postgraduate academic environment, of the reality continuous training of teachers through teaching practice. Specifically in how the experience report contributes to the training of other teachers who will read the report and with the one who is reporting, with the possibility of reflecting on their own practice. Research has shown the following results: many researchers describe themselves in their reports, that is, it is not known the formation or area of activity of the teacher who wrote the research. Another result is the lack of description of the planning, so it is necessary to verify what was the plan initially outlined and whether it was possible to execute it or not. If not, it is important to describe the reasons.